STUDI FENOMENOLOGI MEDIA SOSIAL DAN PERILAKU KONSUMERISME GENERASI Z - Syarif Hidayat; Vivi Candra; Supriyanto; Bambang Arianto; Debi Eka Putri (Program Studi Magister Ilmu Manajemen Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2024)
Objective. This study aims to elaborate on the existence of social media and the increase in consumer behavior for generation Z. The digital era has made social media have greatly influenced all aspects of citizen life, to the point of creating dependency for generation Z. Research Method. This study involved three subjects who were generation Z active users of Instagram and Tiktok social media. This study uses a phenomenological study approach with the Interpretative Phenomenological Analysis analysis method. Data were obtained through in-depth interviews and observations with categories based on statements from research subjects who actively use social media in their daily activities. Results. The results of this study found that social media greatly contributed to the creation of consumer behavior and changes in the behavior of generation Z. Conclusion. Subjective experiences in interacting with social media have played an important role in creating changes in consumer behavior among generation Z. Thus, social media has become a new space that emphasizes consumer behavior for generation Z.